Workplace domestic violence leave laws: implementation, use, implications. Issue 2 (8th June 2015) - Laharnar, Naima; Perrin, Nancy; Hanson, Ginger; Anger, W. Kent; Glass, Nancy
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Intimate partner violence (IPV), affecting 30 percent of women worldwide, may affect employment and workplace safety. In all, 16 US states adopted laws providing leave for employed survivors. These qualitative findings are from an evaluation of Oregon's state leave law. The paper aims to discuss these issues. Design/methodology/approach – The authors interviewed Oregon government employees (n=17) with past year IPV and Oregon supervisors (n=10) of past year IPV survivors. Interviews were transcribed, analyzed and coded. Findings – Participants agreed that IPV has an effect on work. They reported positive workplace reactions to IPV disclosure (93 percent positive, 52 percent negative), but also negative reactions (lack of information, confidentiality, supervisor support). Several implications for supervisors were named (workload, being untrained, being a mandatory reporter, workplace safety and confidentiality). Three years after implementation, 74 percent of participants did not know the leave existed, 65 percent of survivors would have used it if known. The main barriers to usage were fear for job, lack of payment, and stigma. The main barriers of implementation were untrained supervisors and lack of awareness. Participants (85 percent) suggested workplace training on IPV, the law and supervisor role. Practical implications – Effective implementation and support of the IPV leave law is important to avoid negative consequences for survivors and the workplace. Participants called for an increase in IPV awareness and supervisor training. Originality/value – These results provide important recommendations to policymakers, authorities and advocates on development, implementation and evaluation of laws adopted to support employed IPV survivors.